Environmental externalities of the nickel industry: A case study of Morowali and Halmahera, Indonesia - Oskar Vitriano (CV. Literasi Indonesia, 2026)
Indonesia’s rapid expansion of nickel mining and downstream processing has positioned the country as a key supplier for the global energy transition, yet it has also generated significant environmental externalities. This study examines how nickel industrialization produces cumulative environmental impacts through interconnected transmission pathways and how these impacts affect ecosystems, human health, and biodiversity. Using a qualitative, pathway-based analytical framework, the research synthesizes peer-reviewed literature indexed in Scopus, policy and regulatory documents, environmental reports, and spatial evidence, with a focus on major nickel-producing regions such as Morowali, Halmahera, and Raja Ampat. The findings demonstrate that environmental externalities in the nickel sector are systemic rather than isolated. Air pathways transmit particulate matter and gaseous emissions that degrade terrestrial ecosystems and increase health risks. Water pathways convey heavy metals and sediments into riverine and coastal systems, undermining aquatic ecosystem functions, food security, and public health. Land pathways drive deforestation, soil degradation, and habitat fragmentation, resulting in long-term losses of ecosystem services and biodiversity. These impacts interact across pathways, producing cumulative and spatially dispersed effects that disproportionately burden local communities. By integrating multiple environmental pathways and receptors, this study addresses a critical gap in existing literature that has largely relied on sectoral or single-impact analyses. The results underscore the need for integrated, pathway-aware governance approaches to internalize environmental costs and support sustainable nickel-led development.